Abepura District Garbage Transport Route Analysis Jayapura City Papua - Bahtiar, Bahtiar; P., Hermawati. (Budapest International Research and Critics University, 2021)
The increase in the population in Jayapura, followed by an increase in the amount of waste produced, needs to be supported by efficient transportation facilities and infrastructure. The cause of the condition of the accumulation of waste in several areas after the daily transportation schedule is carried out is the limited fuel cost and transportation routes that are less effective and efficient. The purpose of this research is to know efficient waste transportation. From the results of the analysis, the route generated by using the savings matrix calculation for each dump truck managed to save the distance of 0.5 km-3.5 Km, saving fuel costs of Rp. 125,469 - 351,313 /truck-year, and save on fuel costs of Rp. 878,281/Year. The results obtained for the needs of waste transport vehicles and the frequency of rites needed by the Abepura District are 14 units of dump trucks with 2 repetitions, and 5 units of arm roll trucks with 3 repetitions.